Oncolytic effect of Newcastle disease virus is attributed to interferon regulation in canine mammary cancer cell lines. (30th April 2021) - Santos, Mariana Rodrigues; Xavier, Pedro Luiz Porfírio; Pires, Pedro Ratto Lisboa; Rochetti, Arina Lázaro; Rosim, Daniele Fernanda; Scagion, Guilherme Pereira; de Campos Zuccari, Debora Aparecida Pires; Munir, Muhammad; Ferreira, Helena Lage; Fukumasu, Heidge
Abstract: Canine mammary carcinoma (CMC) is one of the major health threats in dogs. The oncolytic virotherapy is a promising strategy to treat canine as well as human cancer patients with non‐pathogenic replicating viruses. Here, we evaluated the antitumor activity of one lentogenic, non‐lytic Newcastle disease virus (NDV) LaSota strain expressing GFP (NDV‐GFP) on five different CMCs and one non‐tumorigenic cell line, regarding cell viability, cell death, selectivity index, morphology, global and target gene expression analysis. As evidenced by the selectivity index, all CMC cell lines were more susceptible to NDV‐GFP in comparison with the non‐tumorigenic cells (~3.1× to ~78.7×). In addition, the oncolytic effect of NDV‐GFP was more evident in more malignant CMC cells. Also, we observed an inverse association of the IFN pathway expression and the susceptibility to NDV. The downregulated genes in NDV‐GFP‐sensitive cells were functionally enriched for antiviral mechanisms by interferon and immune system pathways, demonstrating that these mechanisms are the most prominent for oncolysis by NDV. To our knowledge, this is the first description of oncolysis by an NDV strain in canine mammary cancer cells. We also demonstrated specific molecular pathways related to NDV susceptibility in these cancer cells, opening the possibility to use NDV as a therapeutic‐targeted option for more malignant CMCs. Therefore, these results urge for more studies using oncolytic NDVs, especially considering genetic editing to improve efficacy in dogs.